Pengaruh Perubahan Penggunaan Lahan terhadap Sifat Biofisik Tanah dan Kapasitas Infiltrasi di Kota Malang - Sugeng, Utaya (Muhammadiyah University Press, 2018)
Land use management causes the changes of the function of the land in the city. The change of the function of uncultivated land to be cultivated land has a potential to change soil biophysical characteristic, and at the same time, it decreases the absorption of soil water. This research aims: (1) to study the influence of the landuse change towards soil biophysical characteristics, (2) to study the correlation between soil biophysical characteristics and infiltration capacity, and (3) to study the influence of the landuse change towards the infiltration capacity. The landuse change is studied by comparing the ongoing mapping documents. Soil biophysical characteristics consist of root biomass, number of worms, soil organic matter (SOM), and porosity. The root biomass is obtained by root density, the number of worms is identified with monolith and hand sorting method, the SOM is identified with fraction analysis, and the porosity is identified with cylinder and pignometer method. The water absorption is measured with the plot experiment. The influence of the landuse towards soil biophysical traits is analyzed T-test and the influence of landuse change towards infiltration capacity is analyzed correlatively. This research gains the results that: (1) the landuse change causes the change of soil biophysical traits, too, and the soil biophysical traits change causes, furthermore, the declining of the land capability in absorbing water, and (2) the amount of the infiltration capacity is caused by soil biophysical traits, mostly by root biomass, number of worms, and the SOM, and (3) the landuse change causes the declining of infiltration capacity.